2022
DOI: 10.1021/acssuschemeng.1c07028
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Performance in the Production and Use of Recovered Fertilizers from Organic Wastes Treated by Anaerobic Digestion vs Synthetic Mineral Fertilizers

Abstract: Recovered fertilizers (RFs), in the form of digestate and digestate-derived ammonium sulfate, were produced from organic wastes by thermophilic anaerobic digestion (AD) at full scale. RFs were then used for crop production (maize), substituting synthetic mineral fertilizers (SFs). Environmental impacts due to both RF and SF production and use were studied by a life cycle assessment (LCA) approach using, as much as possible, data directly measured at full scale. The functional unit chosen was referred to as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Studies that assessed the environmental and economic impacts of treating liquid and solid digestate from anaerobic digestion comprised 13% of all the LCA and LCCA/TEA studies reviewed (Figure b and Table S10). LCA studies focused on biogas production from anaerobic digestion integrated with treatment of the liquid digestates to recover nutrients via struvite precipitation and ammonia stripping , utilizing municipal sewage sludge and animal waste as feedstocks. These studies were conducted by applying CML and ReCiPe in European countries and using TRACI in the USA.…”
Section: Applications Of Data Science In Rrcc From Organic Waste Streamsmentioning
confidence: 99%
“…Studies that assessed the environmental and economic impacts of treating liquid and solid digestate from anaerobic digestion comprised 13% of all the LCA and LCCA/TEA studies reviewed (Figure b and Table S10). LCA studies focused on biogas production from anaerobic digestion integrated with treatment of the liquid digestates to recover nutrients via struvite precipitation and ammonia stripping , utilizing municipal sewage sludge and animal waste as feedstocks. These studies were conducted by applying CML and ReCiPe in European countries and using TRACI in the USA.…”
Section: Applications Of Data Science In Rrcc From Organic Waste Streamsmentioning
confidence: 99%
“…Several LCA studies reported better environmental impacts for the agriculture use of treated sewage sludge respect chemical fertilizers (Herrera et al, 2022;Di Maria et al, 2016;Chiew et al, 2015;Tidåker et al, 2006;Suh and Rousseaux, 2002;Hareder et al, 2017;Hospido et al, 2005;Brockmann et al, 2018;Muñoz et al, 2017;Chiu et al, 2016).…”
Section: Lca Studiesmentioning
confidence: 99%
“…High fluxes (50-100 L m −2 h −1 (LMH)) occurred when VSEP was used to control the deposition of colloidal silica on the membrane surface. 11 VSEP has already been commercialized in recovering nutrient concentrate from pig slurry 12 and reducing magnetic ion exchange concentrate volume. 13 DTRO has a plate-andframe configuration with large feed channels and a shorter flow path, which creates high turbulence, thus alleviating the membrane fouling potential.…”
Section: Introductionmentioning
confidence: 99%